RECOMBINANT HUMAN LUTEINIZING HORMONE FOR THE TREATMENT OF INFERTILITY: THE GENERATION OF PRODUCER CELL LINES - N. A. Orlova; S. V. Kovnir; Yu. A. Khodak; M. A. Polzikov; I. I. Vorobiev (IRBIS LLC, 2017)
The aim of the study was to obtain the cell line secreting the maximum amounts of the human luteinizing hormone (LH) heterodimer without significant amounts of free LH alpha-subunit.Materials and methods. A pair of original plasmids of the p1.1 family containing long non coding segments of the Chinese hamster translation elongation factor 1 alpha gene and a fragment of the concatemer of the Epstein-Barr virus long terminal repeat were used for the persistent expression of human LH subunit genes in Chinese hamster ovary cells. The open reading frame areas of the LH subunits genes were cloned into vectors with the dihydrofolate reductase (DHFR) or glutamine synthase (GS) genes, transfected into the cells, and amplified by methotrexate; following the final procedure of limiting dilution, clonal producer cells were obtained.Results. For a pair of plasmids, where the LH alpha subunit gene was associated with GS and the beta subunit gene was associated with DHFR, the rate of LH production by the initial stably transfected cell population was 0.1 pg/cell/day and the doubling time was 37 hours, for the reverse pair of plasmids - 0.3 pg/cell/day and 48 hours, respectively. For the initial cell population and for their clonal lines, we used increasing concentrations of methotrexate to amplify the genetic cassettes in the cell genome. In the polyclonal population an increase in the cell productivity up to 2.2 μg/106 cells was observed at a concentration of methotrexate 8 μM; for the clonal lines - a significant productivity increase up to 0.09 μg/106 cells was achieved in only one of six cell lines. Conclusion. Cell lines secreting significant amounts of heterodimeric LH without a significant admixture of free subunit can be obtained using a pair of plasmid vectors encoding the LH subunit genes and the selection markers DHFR or GS. Co-transfection of the plasmids and their subsequent amplification in the genome of producer cells under the selective pressure of methotrexate results in a significant increase in the biosynthesis rate of both LH subunits. The present study provides a rationale for a potential use of these lines in the industrial production of human luteinizing hormone.